2019
DOI: 10.1186/s12957-019-1683-8
|View full text |Cite
|
Sign up to set email alerts
|

Should internal mammary lymph node sentinel biopsy be performed in breast cancer: a systematic review and meta-analysis

Abstract: Purpose Results from studies of internal mammary lymph node sentinel biopsy are inconsistent. Methods A comprehensive literature search was conducted in MEDLINE, EMBASE, Scopus, Cochrane database, and Clinical Trials. Studies reporting the rate of internal mammary lymph node sentinel biopsy (IMN-SLNB) positivity were identified. We performed pooled proportion meta-analysis using random-effects meta-analyses. The correlation of IMN and axillary lymph node (AXN) metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…All SNs identified with either methyl blue or radioactive compounds should be sent for frozen sectioning. Furthermore, metastasis in the internal mammary lymph nodes is possible in high-risk patients, and preoperative biopsy should be considered [ 24 , 25 ]. We did not perform sentinel biopsy for the internal mammary lymph nodes, and underestimating nodal staging should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…All SNs identified with either methyl blue or radioactive compounds should be sent for frozen sectioning. Furthermore, metastasis in the internal mammary lymph nodes is possible in high-risk patients, and preoperative biopsy should be considered [ 24 , 25 ]. We did not perform sentinel biopsy for the internal mammary lymph nodes, and underestimating nodal staging should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…While difficult relative to axillary sentinel LN biopsy, the success rate for IMLN biopsy currently averages 90% for experienced teams [52][53][54][55]. Thoracoscopic IMLN dissection in breast cancer has also been reported with the same positive IMLN rate and less morbidity than the conventional intercostal space incision [9,56].…”
Section: Histopathologically Confirmed Imln Metastasismentioning
confidence: 99%
“…Relative to lymphoscintigraphy alone, SPECT/CT provides advantages in terms of accurate anatomical localization, identification of false-positive results, fewer false-negative results, and better guidance regarding the surgical approach. Using lymphoscintigraphy and SPECT/CT after an intra-lesion injection of 99mTc-nanocolloid, the sentinel IMLN was found to contain metastasis in only 24% of patients from a pilot study [ 60 ] and in 34% of patients from a Dutch multicenter study [ 55 ]. The Breast Cancer Center of Shandong Cancer Hospital optimized the use of 99mTc-labeled sulfur colloid (99mTc-SC) in sentinel IMLN mapping and detection, evaluated the SPECT-CT image acquisition time, and modified the injection technique (peri-areolar intraparenchymal, high volume, and ultrasound guidance), which increased the IM-SLN visualization rate to 71.9% for breast cancer patients who were receiving initial surgery [ 52 , 57 , 58 , 62 , 63 ].…”
Section: Minimally Invasive Diagnosis Of Im-slnbmentioning
confidence: 99%
“…Studies have shown that LN resection and radiotherapy are valuable for prognosis, but the NSABP B04 trial showed that late resection did not affect prognosis (11,16). Although de-escalation of axillary surgery is fairly common, for patients with negative LN status (N0), many studies have stated that ALND is not beneficial for sentinel LN-negative patients (17)(18)(19). Our mathematical modeling results suggest that nodal metastasis is not merely a straightforward process of BC, but has a complex effect on prognosis that can also be altered by treatment.…”
Section: An Additional Adjustment Was Made By Upgrading Stagementioning
confidence: 99%